Assessment of mass transfer in the stagnant liquid regions in trickle-bed reactors - Mocciaro, Clarisa (2011)
A critical revision has been carried out of experimental investigations to quantify the size of the liquid stagnant region in fixed beds with co-current gas-liquid down-flow, and its ability to exchange mass with the dynamic region and with the particle surface. The revision has exposed that a high level of uncertainty arise to estimate, particularly, the mass exchange rate from the available evidence. Therefore, a second purpose is to introduce a geometric model to represent the stagnant region for spherical particles from which, assuming that diffusion is the only mass transport mechanism, it becomes possible to estimate the mass exchange rates with the dynamic region and with the particle surface. Finally, it was discussed why to expect that the geometric model is able to provide a lower bound to mass exchange rate with the dynamic region and a tight lower bound to mass exchange rate with the catalyst surface.